Application of Selenium Can Alleviate the Stress of Cadmium on Rapeseed at Different Growth Stages in Soil - Lingli Nie; Bingqian Zhou; Bo Hong; Xiaodan Wang; Tao Chang; Chunyun Guan; Mei Guan (Agronomy, 2023)
Cadmium (Cd) stress greatly limits the growth of rapeseed, and selenium is a micronutrient that is essential for rapeseed growth, but whether and how selenium application alleviates Cd-induced inhibition remains poorly understood. The present study investigated the alleviating effects of exogenous selenium on rapeseed growth under cadmium (Cd) stress based on the aspects of agronomic traits and soil bacterial community structure and diversity. The results show that low-selenium treatment increased the rapeseed yield by 20.92% by increasing the number of pods per plant under Cd stress, but such effects were not prominent when the selenium application rate was high. Meanwhile, selenium application significantly reduced the cadmium content by 4.74–26.89% in different organs of rapeseed. Further analysis suggested that the benefits of selenium in alleviating Cd stress might be induced by changes in soil bacterial community structure and diversity. In addition, in the functional metabolism spectrum of rapeseed microorganisms treated with selenium, there were 5 primary metabolic pathways with significant differences, and there were 32 and 169 pathways for secondary and tertiary metabolic pathways, respectively. Therefore, selenium treatment in rapeseed soil can alter the composition and metabolic function spectrum of soil microbial communities, ultimately affecting plant growth and Cd tolerance.